2011
DOI: 10.1530/eje-11-0128
|View full text |Cite
|
Sign up to set email alerts
|

Response of biochemical markers of bone turnover to oral glucose load in diseases that affect bone metabolism

Abstract: Objective: Postprandial suppression of bone resorption is considered one of the main contributors in the circadian rhythm of bone turnover markers. The aim of this study was to investigate this physiological response of bone tissue in diseases that affect bone metabolism. Patients and methods: In this study, 118 patients (45 hypothyroid, 40 hyperthyroid, and 33 b-thalassemic patients) and 78 healthy individuals matched for age and body mass index were included. An oral glucose test (75 g glucose) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The postprandial response of bone turnover is expressed as the percent change from baseline at 2 h after oral glucose for CTX-I and P1NP, as previously described [20,21] . The differences between patients and controls were assessed using a two-tailed Student's t-test or the non-parametric MannWhitney U test for independent samples, as appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The postprandial response of bone turnover is expressed as the percent change from baseline at 2 h after oral glucose for CTX-I and P1NP, as previously described [20,21] . The differences between patients and controls were assessed using a two-tailed Student's t-test or the non-parametric MannWhitney U test for independent samples, as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have investigated the postprandial response of bone resorption in patients with type 2 diabetes mellitus [20] , thyroid diseases and beta-thalassemia major [21] , that are very often complicated with low bone mass and increased fracture risk. It has been shown that the postprandial suppression of bone resorption in patients with overt diabetes is significantly attenuated, suggesting an additional contributing factor in the deterioration of bone quality and bone mass observed in these patients [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial suppression of bone resorption is considered one of the main contributors in the circadian rhythm of bone turnover markers. Accordingly, after oral glucose load, a reduction was observed for BTM, especially CTX (46.9% for β-CTX, 7.9% for P1NP, and 8% for OC) [12].…”
Section: Biological and Pre-analytical Variabilitymentioning
confidence: 91%
“…Two recent studies have investigated this phenomenon in patients with type 2 diabetes mellitus, 16 thyroid diseases and beta-thalassemia major, 17 all conditions that are very often complicated with low bone mass and increased fracture risk. It has been shown that the suppression of postprandial bone resorption is attenuated in patients with overt diabetes but not in those with impaired glucose tolerance (IGT), suggesting an additional contributing factor in the deterioration of bone quality and bone mass seen in diabetes.…”
Section: Postprandial Variation Of Bone Turnovermentioning
confidence: 99%